2017
DOI: 10.1016/j.bone.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cbl-PI3K interaction modulates the periosteal response to fracture by enhancing osteogenic commitment and differentiation

Abstract: The periosteum contains multipotent skeletal progenitors that contribute to bone repair. The signaling pathways regulating the response of periosteal cells to fracture are largely unknown. Phosphatidylinositol-3 Kinase (PI3K), a prominent lipid kinase, is a major signaling protein downstream of several factors that regulate osteoblast differentiation. Cbl is an E3 ubiquitin ligase and a major adaptor protein that binds to the p85 regulatory subunit and modulates PI3K activity. Substitution of tyrosine 737 to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 54 publications
(74 reference statements)
1
22
0
Order By: Relevance
“…PI3K-AKT activity regulates activation of several transcription factors. We have previously reported that in YF mice enhanced AKT activity is responsible for upregulation of Sp7 activation, resulting in increased bone formation during fracture healing ( Scanlon et al, 2017 ). Sp1 transcriptional activity is also dependent on PI3K activation ( Chu, 2012 ; Zhang et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PI3K-AKT activity regulates activation of several transcription factors. We have previously reported that in YF mice enhanced AKT activity is responsible for upregulation of Sp7 activation, resulting in increased bone formation during fracture healing ( Scanlon et al, 2017 ). Sp1 transcriptional activity is also dependent on PI3K activation ( Chu, 2012 ; Zhang et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that knock-in mice harboring the Y737F mutation (YF mice) have increased PI3K-AKT activation ( Adapala et al, 2010a , Adapala et al, 2010b , Adapala et al, 2014a ; Scanlon et al, 2017 ). YF mice increased bone volume due to a combination of increased non-resorptive osteoclasts and increased bone formation by osteoblasts ( Adapala et al, 2010a ; Brennan et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In several self‐renewing and regenerative tissues, such as muscle, intestine, and hair follicles, definitive markers have been established to enable identification and characterization of resident stem cell populations and their in vivo activity . Similarly, major advances have been made for bone marrow derived mesenchymal stem cells (BMSCs), adipose stem cells, and periosteal cells . In contrast, while stem/progenitor cells have been identified for tendons (frequently termed TSPCs), there remains a paucity of information regarding distinguishing markers, making it challenging to study these cells in vivo.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Similarly, major advances have been made for bone marrow derived mesenchymal stem cells (BMSCs), adipose stem cells, and periosteal cells. [11][12][13][14][15][16][17][18][19] In contrast, while stem/progenitor cells have been identified for tendons (frequently termed TSPCs), there remains a paucity of information regarding distinguishing markers, making it challenging to study these cells in vivo. Given the molecular and structural similarities between tendons and ligaments, [20][21][22] we will focus this review on tendon and TSPCs, since the majority of the literature is concentrated on tendon biology.…”
mentioning
confidence: 99%
“…The periosteum is also known to be a reservoir of quiescent mesenchymal progenitor cells, which are activated upon injury. These cells differentiate to form cartilage and bone and thereby repair bone injury . The periosteum is a highly vascularized tissue and has been shown to contain myeloid cells of the hematopoietic lineage, such as tartrate‐resistant acid phosphatase (TRAP) cells .…”
Section: Introductionmentioning
confidence: 99%